Peran Benteng Vredeburg Dalam Peristiwa Agresi Militer Belanda II Dan Serangan Umum 1 Maret Tahun 1948-1949 - Azriel Satria Mukti; Muhammad Iqbal Birsyada (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to determine the condition of Fort Vredeburg during the colonial period and its role in the Balanda II Military Aggression and the March 1 General Attack. What is used is the literary method using steps: heuristics, verification or source criticism. There are two steps that need to be taken, namely external criticism and internal criticism. The next interpretation is a series of histories based on sequence and history. Compilation is compiling data obtained from sources into a scientific work according to the title. Vredeburg Fort is part of the long history of the city of Yogyakarta, the condition of Vredeburg Fort during the colonial period as a defensive fortress and as a place of government for the Dutch, Japanese and Indonesian. The role of Fort Vredeburg in the Dutch Military Aggression II in 1948 as a defense base for the Indonesian army and was successfully captured by the Dutch. When the General Attack of 1 March 1949 took place, Fort Vredeburg became the center of Dutch defense and became the main target of the General Attack of 1 March 1949 in Yogyakarta.